Implementing Consumer-based, Internet of Things-based Environmental Monitoring Systems within Smart Spaces - Renaldi Gondosubroto (School of Industrial and System Engineering, Telkom University, 2018)
Internet of Things (IoT) based Air quality measurement systems within smart cities have long been researched to find the most efficient way of collecting data for mitigation purposes in various areas. One of the biggest issues is the balance between flexibility and size for consumer-based measuring devices. This paper talks about a customized design of such a device, measuring nine different parameters that are considered crucial in any environment (CO2, CO, PM 1.0, PM 2.5, PM 10, temperature, humidity, pressure and altitude). This data is then communicated from the microcontroller through the Wi-Fi module attached to be able to access the data at a Graphical User Interface (GUI) made on GReS Studio’s website or also through other third-party services such as ThingSpeak. Analysis of a sample of the results obtained is also discussed. Keywords-Internet of Things, Smart City